AVOIDING COMMON ERRORS IN ACADEMIC WRITING - Mayliyeva Zilola Ollabergan qizi; Tog’ayeva Umida Ernazarovna (TADQIQOTLAR.UZ, 2024)
Abstract:  Lack of focus and clarity in writing can be a common problem for many writers, but it can be remedied with some simple techniques. With a lack of focus, you cannot make your readers stay focused on the topics. In addition, if there is no clarity, you fail to convey the intended message to readers.